The covenant in Judaism and Paul : a study of ritual boundaries as identity markers - Christiansen, Ellen Juhl. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1995)
The Covenant in Judaism and Paul deals with biblical and intertestamental uses of covenant and related rituals, challenging the view that baptism replaces circumcision, since baptism is entry into the new covenant, and showing that ritual boundaries are replaced or redefined since identity has changed. The investigation uses social categories, "identity" as a term that offers an explanation for a group's selfunderstanding and "boundary" as a term for entry rite of affirmation marker. Part A looks at the Old Testament background to aspects of the covenant. Part B examines covenant identity and rituals in Palestinian Judaism as featured in Jubilees, the Temple Scroll, the Damascus Document, and the Community Rule. It includes a brief analysis of the baptism administered by John the Baptist. Part C analyses Paul's views on covenant, circumcision, and baptism against this background.